Evaluasi Kecernaan Bahan Kering Bahan Organik dan Protein Kasar Kombinasi Jerami Padi dan an Tithonia Fermentasi Secara In-Vitro - Sari, Yesi Paramita; astuti, tri; Asri, Alfian (Jurnal Peternakan Mahaputra, 2023)
This research aims to determine the effect of fermentation time for rice straw and tithonia (Tithonia diversifolia) on the in-vitro digestibility of dry matter, organic matter, and crude protein as ruminant feed ingredients. The experiment was carried out using a Randomized Block Design with 4 treatments and 4 groups. The treatments in this study were a combination of rice straw and tithonia without fermented by local microorganisms (P0) as a control, a combination of rice straw and tithonia by local microorganisms and 0 days incubation (P1), a combination of rice straw and tithonia by local microorganisms and length incubated for 7 days (P2). , a combination of rice straw and tithonia by local microorganisms was length incubated for 14 days (P3). Based on the results of statistical analysis, shows that the fermentation time of rice straw and tithonia (Tithonia diversifolia) with local microorganisms in the contents of the cow's rumen has an insignificantly different effect (P>0.05) on dry matter digestibility and crude protein digestibility and had a very significant effect (P<0.01) on the digestibility of organic matter.